Electrosynthesis of Titanium Alloys from Spent SCR Catalysts - Long Zheng; Jiahao Jin; Zongying Cai; Xiangpeng Li; Qi Zhu; Weigang Cao (Crystals)
Spent selective catalytic reduction (SCR) catalysts are hazardous wastes containing many valuable metals whose improper disposal can cause environmental pollution and resource waste. Therefore, it is significant to recover valuable metals from spent SCR catalysts. In this study, the molten salt electrolytic method was employed to treat the SCR catalyst to direct electrosynthesis titanium alloys, which is more environmentally friendly and economical to obtain metal or alloy from secondary resources. A systematic investigation was carried out via experimental analysis and thermodynamic calculation. The results show that high-temperature pretreatment induces the aggregation of W and the formation of CaWO4. Through molten salt electrolysis, titanium alloys containing Ti(W) and Ti5Si3 were formed, with a metal recovery rate of 80–87%. The electrolytic process and the reaction mechanism were also investigated. It is suggested that the molten salt electrolytic method is an effective way to recover valuable metals from spent SCR catalysts.